Relationality is not WEIRD: the importance of relational thinking in the majority of the planet’s societies - Rachelle K. Gould; Yolanda Jimenez Naranjo; Patricia Balvanera (Ecosystems and People)
The W.E.I.R.D. acronym refers to populations that are Western, Educated, Industrialized, Rich, and Democratic. The concept emerged with scholars’ realizations that much psychological research makes universal claims based on work with WEIRD participants, despite the fact that WEIRD cultures are globally unusual. We note a related trend in sustainability science and practice: WEIRD psychological tendencies (and related institutions and assumptions) tend to dominate in global sustainability policy/practice. In this paper, we explore one set of potential implications of this dominance via a focus on psychological differences that relate to an emerging focal interest in sustainability science: relationality. We show that many non-WEIRD psychological tendencies are more relational than their WEIRD counterparts. We then assess how these differences relate to seven key features of sustainability. We identify how non-WEIRD relationality is likely to contribute to sustainability in unique ways and discuss research gaps that preclude full understanding of the implications of a WEIRD (and therefore less relational) focus. To illustrate connections between non-WEIRD psychological tendencies and sustainability, we offer the example of the perspective of comunalidad, of the original peoples of Oaxaca, Mexico. This perspective is reflected in a new Oaxacan regional university. Our analysis overall suggests that a focus on WEIRD psychology (even, or perhaps especially, if implicit) omits or underplays many forms of more relational thinking, which are likely associated with sustainability.